The ugly and the bad: banking and housing crises strangle output permanently, ordinary recessions do not - Jens Boysen-Hogrefe; Nils Jannsen; Carsten-Patrick Meier (Kiel Institute for the World Economy (IfW), 2010)
This paper provides statistical evidence suggesting that in industrial countries, recessions that are associated with either banking crises or housing crises dampen output far more than ordinary recessions. Using a parametric panel framework that allows for a bounceback of the level of output in the course of the cyclical recovery, we find that ordinary recessions are followed by strong recoveries that make up for almost all the preceding shortfall in output. This bounceback tends to be significantly smaller following recessions associated with banking crises or housing crises. Our paper corroborates the practice of focusing exclusively on severe crises used in an emerging macroeconomic literature and integrates it with the earlier literature on recessions and recoveries.
Keywords: E32; C33; 330; Business cycle; banking crisis; housing crisis; panel data; asymmetry; persistence